The percentage of Body Fat and its Relationship with Blood Pressure in Adults from Rural and Urban Areas - Carlos Enrique García Yerena; Omar Oliveros Rangel; Brian Johan Bustos Viviescas; Amalia Villamizar Navarro; John Alexander García Galviz (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Foundation: excess body fat is marked by a permanent imbalance between food consumption and energy expenditure of human beings that generate various health risks, including increased blood pressure. Objective: determine the relationship between the percentage of body fat and blood pressure in adults from rural and urban areas of the municipality of Carmen de Chucurí, Colombia. Method: a descriptive and correlational study with a quantitative approach was carried out on a randomly chosen sample, composed of 406 subjects for the inhabitants of the rural sector and 409 of the urban sector between 18 and 40 years of age from the Carmen Chucurí municipality. Body mass was evaluated, with the use of the tool called electrical impedance and the OMRON HBF-514C brand equipment, and blood pressure and the OMRON HEM-4030 digital blood pressure monitor was used. Results: the main finding of this research was the positive and significant association between the percentage of body fat and diastolic blood pressure in rural men and women in the Carmen de Chucurí municipality. Conclusions: the percentage of body fat is positively and significantly associated with diastolic blood pressure in rural men and women of the Carmen de Chucuri municipality; for the other parameters analyzed, a significant correlation was not evident.